2019
DOI: 10.1097/md.0000000000016577
|View full text |Cite
|
Sign up to set email alerts
|

Delayed closure of macular hole secondary to Terson syndrome after vitrectomy

Abstract: Rationale: Macular hole (MH) is a rare complication of Terson syndrome. Delayed closure of persistent MH after pars plana vitrectomy (PPV) is occasionally reported in literature, none of them is MH secondary to Terson syndrome. We describe a case of MH secondary to Terson syndrome and delayed closure occurred after PPV, and we also study the characteristics of delayed closure of persistent MH by reviewing related literatures. Patient concerns: A 61-year-old man presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…8,9 To better understand the characteristics of an MH secondary to Terson syndrome, we conducted a literature search. We found that an MH secondary to Terson syndrome was observed in only nine eyes in seven articles 4,6,[10][11][12][13][14] (Table 1). Although MH occasionally occurs as a complication of Terson syndrome, the exact cause is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 To better understand the characteristics of an MH secondary to Terson syndrome, we conducted a literature search. We found that an MH secondary to Terson syndrome was observed in only nine eyes in seven articles 4,6,[10][11][12][13][14] (Table 1). Although MH occasionally occurs as a complication of Terson syndrome, the exact cause is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Terson syndrome is defined as the presence of intraocular haemorrhage associated with intracranial haemorrhage and elevated intracranial pressure. 6 Based on the location of the haemorrhage, the clinical classification of intraocular haemorrhage can be categorized as sub-ILM, preretinal, intraretinal, subhyaloid, or intravitreal. 7 The physiopathology of Terson syndrome and the origin of intraocular blood remain controversial.…”
Section: Discussionmentioning
confidence: 99%
“…[10] It is well-accepted that the mechanism of MH is tangential anterior-posterior traction of the vitreomacular or macular ILM. [11] Moreover, a sudden bloody dissection of the ILM may produce tractional forces responsible for causing MH. In this case, the ILM was not peeled surgically.…”
Section: Discussionmentioning
confidence: 99%
“…1 It has been shown in the literature that such FTMHs can close spontaneously in many different clinical scenarios. 2 Distelmaier et al reported that a FTMH can recur following surgical repair but it was closed without any intervention. 3 Spontaneous closure has also been reported in context of posterior uveitis, cystoid macular oedema, 4 and following retinal detachment repair by pars plana vitrectomy.…”
Section: Dear Editormentioning
confidence: 99%
“…Formation of FTMH following vitrectomy is rare with its incidence being reported as 0.24% [ 1 ]. It has been shown in the literature that such FTMHs can close spontaneously in many different clinical scenarios [ 2 ]. Distelmaier et al [ 3 ] reported that a FTMH can recur following surgical repair but it was closed without any intervention.…”
mentioning
confidence: 99%